REKONSTRUKSI MODEL PEMURIDAN KONTEKSTUAL DALAM PELAYANAN MISI DI KAMBOJA (Tarombo: Journal of Christian Theology, Education, and Ministry, 2026)
ABSTRACTThis study addresses the failure of Western-derived discipleship models in Cambodia, a post-conflict context marked by collective trauma, Theravada Buddhist-animist syncretism, and high collectivism. Despite initial conversions, anecdotal reports indicate low retention and persistent syncretic practices, yet systematic data on retention rates remain unavailable. The research gap lies in the absence of an integrated model that combines trauma healing, collective identity reconstruction, and narrative approaches for Southeast Asian mission fields. Through a systematic literature review synthesizing missiology, cultural anthropology, and social psychology, this study critiques existing frameworks—such as Hiebert’s critical contextualization and Kraft’s dynamic equivalence—for their cognitive bias and neglect of affective and social dimensions. The novelty is the Contextual Discipleship Reconstruction Framework (CDRF), a three-layered model: incarnational theology, Cambodian cultural anthropology (collectivism, syncretism), and post-traumatic social psychology. CDRF offers a testable framework that bridges theoretical gaps and provides practical guidance for mission practitioners and curriculum developers in Cambodia and analogous contexts. The study contributes to missiological theory by proposing an empirically verifiable model specific to post-conflict, syncretic societies.Keywords: contextual discipleship; Cambodia mission; trauma healing; syncretism; collective identityABSTRAKPenelitian ini mengatasi kegagalan model pemuridan yang berasal dari Barat di Kamboja, konteks pasca-konflik yang ditandai trauma kolektif, sinkretisme Buddha Theravada-animisme, dan kolektivisme tinggi. Meskipun terjadi pertobatan awal, laporan anekdotal menunjukkan retensi rendah dan praktik sinkretis yang menetap, namun data sistematis mengenai tingkat retensi belum tersedia. Kesenjangan penelitian terletak pada ketiadaan model terintegrasi yang menggabungkan penyembuhan trauma, rekonstruksi identitas kolektif, dan pendekatan naratif untuk ladang misi Asia Tenggara. Melalui tinjauan literatur sistematis yang mensintesis misiologi, antropologi budaya, dan psikologi sosial, studi ini mengkritik kerangka yang ada—seperti kontekstualisasi kritis Hiebert dan ekuivalensi dinamis Kraft—karena bias kognitif dan pengabaian dimensi afektif dan sosial. Kebaruan adalah Contextual Discipleship Reconstruction Framework (CDRF), model tiga lapis: teologi inkarnasional, antropologi budaya Kamboja (kolektivisme, sinkretisme), dan psikologi sosial pasca-trauma. CDRF menawarkan kerangka yang dapat diuji secara empiris, menjembatani kesenjangan teoretis dan menyediakan panduan praktis bagi pelayan misi dan pengembang kurikulum di Kamboja dan konteks serupa. Studi ini berkontribusi pada teori misi dengan mengusulkan model spesifik untuk masyarakat pasca-konflik dan sinkretis yang dapat diverifikasi.Kata kunci: pemuridan kontekstual; misi Kamboja; penyembuhan trauma; sinkretisme; identitas kolektif
Keywords: pemuridan kontekstual; misi kamboja; penyembuhan trauma; sinkretisme; identitas kolektif